2018
DOI: 10.29103/ag.v1i1.1077
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Daya Saing Ekspor Komoditas Udang Indonesia

Abstract: This study was conducted to determine the competitiveness and performance of Indonesia to shrimp export commodities also determine the factors that affect the level of competitiveness so as to be a strategy to improve the competitiveness of Indonesian shrimp commodity in the international market. The data that used in this study are primary  and  secondary  data. Tools  of  analysis  used  in  this  study  are Revelead Comparative Advantege (RCA), Literacy Test, and  SWOT  analysis (Strength, Weakness, Opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Another research on competitiveness conducted by Mufa'ah and Hayati revealed that there are 6 provinces in Indonesia that contribute the highest exports of fishery products, East Java at 352,839 tons or an increase of 3.24 percent, DKI Jakarta at 274,762 tons or an increase of 4.29 percent, Maluku by 187,143 tons or an increase of 28.24 percent, South Sulawesi by 91,125 tons or an increase of 1.19 percent, North Sumatra by 77.975 tons or an increase of 10.33 percent, and West Papua by 42.844 or an increase of 15.84 percent [7].…”
Section: Research On Competitiveness Conducted Bymentioning
confidence: 99%
“…Another research on competitiveness conducted by Mufa'ah and Hayati revealed that there are 6 provinces in Indonesia that contribute the highest exports of fishery products, East Java at 352,839 tons or an increase of 3.24 percent, DKI Jakarta at 274,762 tons or an increase of 4.29 percent, Maluku by 187,143 tons or an increase of 28.24 percent, South Sulawesi by 91,125 tons or an increase of 1.19 percent, North Sumatra by 77.975 tons or an increase of 10.33 percent, and West Papua by 42.844 or an increase of 15.84 percent [7].…”
Section: Research On Competitiveness Conducted Bymentioning
confidence: 99%
“…A study conducted by Mufa'ah and Mardiyah [4] stated that Indonesia's shrimp export commodity has strong @ @ @ competitiveness (RCA>1) and increased, these indicating an increase in shrimp export performance between the current year and the previous year in meeting world market demand. Besides that, a study also conducted by Sanny [5] stated that Indonesia's RCA value has always been greater than 1 (one) from 2001 to 2017, shows that Indonesian shrimp commodities have competitiveness in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Pudyastusi et al, (2018) menyatakan bahwa ekspor udang merupakan sub sektor perikanan yang terus mengalami pertumbuhan baik dari sisi permintaan dan penawaran. Daya saing ekspor komoditas ini yang kompetitif menjadi alasan utama dalam menerapkan strategi peningkatan produksi (Mufa'ah & Hayati, 2016).…”
Section: Introductionunclassified